Ciprofloxacin susceptibility testing by MIC and disk elution of drug-resistant Mycobacterium tuberculosis and Mycobacterium avium complex. - LaBombardi, V J (1993)
The ability to provide susceptibility data for certain species of mycobacteria can be clinically useful. In this study, the disk elution method for susceptibility testing was adapted for testing ciprofloxacin against mycobacterial isolates. Of the 75 Mycobacterium tuberculosis isolates tested, including 23 multiply drug-resistant isolates, 96% were susceptible to ciprofloxacin at a breakpoint concentration of 2 micrograms/ml.